Species–area relationships are modulated by trophic rank, habitat affinity, and dispersal ability. Issue 2 (1st February 2015) - van Noordwijk, C. G. E. (Toos); Verberk, Wilco C. E. P.; Turin, Hans; Heijerman, Theodoor; Alders, Kees; Dekoninck, Wouter; Hannig, Karsten; Regan, Eugenie; McCormack, Stephen; Brown, Mark J. F.; Remke, Eva; Siepel, Henk; et al.
Abstract : In the face of ongoing habitat fragmentation, species–area relationships (SARs) have gained renewed interest and are increasingly used to set conservation priorities. An important question is how large habitat areas need to be to optimize biodiversity conservation. The relationship between area and species richness is explained by colonization–extinction dynamics, whereby smaller sites harbor smaller populations, which are more prone to extinction than the larger populations sustained by larger sites. These colonization–extinction dynamics are predicted to vary with trophic rank, habitat affinity, and dispersal ability of the species. However, empirical evidence for the effect of these species characteristics on SARs remains inconclusive. In this study we used carabid beetle data from 58 calcareous grassland sites to investigate how calcareous grassland area affects species richness and activity density for species differing in trophic rank, habitat affinity, and dispersal ability. In addition, we investigated how SARs are affected by the availability of additional calcareous grassland in the surrounding landscape. Beetle species richness and activity density increased with calcareous grassland area for zoophagous species that are specialists for dry grasslands and, to a lesser extent, for zoophagous habitat generalists. Phytophagous species and zoophagous forest and wet‐grassland specialists were not affected by calcareous grassland area. The dependence of species on large single sites increased with decreasing dispersal ability for species already vulnerable to calcareous grassland area. Additional calcareous grassland in the landscape had a positive effect on local species richness of both dry‐grassland specialists and generalists, but this effect was restricted to a few hundred meters. Our results demonstrate that SARs are affected by trophic rank, habitat affinity, and dispersal ability. These species characteristics do not operate independently, but should be viewed in concert. In addition, species' responses depend on the landscape context. Our study suggests that the impact of habitat area on trophic interactions may be larger than previously anticipated. In small habitat fragments surrounded by a hostile matrix, food chains may be strongly disrupted. This highlights the need to conserve continuous calcareous grassland patches of at least several hectares in size.